High-temperature thermal imaging to inform the arc-melt synthesis of nuclear materials - Stone, Jordan; Khair, Mira; Cavazos, Steven; Sooby, Elizabeth (Frontiers in Nuclear Engineering, 2024)
Advancement of nuclear energy technology motivates and necessitates the development of novel materials and synthesis methods to produce materials characteristic of those enabling new fuel cycles. Alongside the maturation of R&D scale technologies to produce these materials, there is an ongoing effort to develop in situ monitoring capabilities to reduce the time to discovery and development of these fuels. Monitoring data can be leveraged in artificial intelligence platforms to detect phenomena which lead to varied macro-and microstructural features which impact the application and performance of samples synthesized. The present study presents early-stage findings of the implementation of high temperature, high frame rate infrared thermal imaging to the monitor arc-melt synthesis of novel fuels and compounds of relevance to advanced nuclear reactors. The study illustrates both the challenges and opportunities of this methodology, highlighting the importance of internal standards, while determining the emissivity and transmission values as well as the visualization of volatilization during melt synthesis.